ANALISIS EFEKTIVITAS PENGAWASAN INTERN KAS PADA DINAS PERBUHUNGAN KOTA MANADO - Buchari, Demmi P.R.D; Ilat, Ventje; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Advancing technology can affect the development of each company or institution, whether private or government. In particular the creation of accountability in government financial performance is an absolute case created by a local chief. Is implicit in the case law (Law) number 17 of 2003 on State Finances, Law number 01 of 2004 on the National Treasury. The research was conducted at the Office of Manado City Relations and discuss the internal control of cash. The purpose of the studywas to determine how the internal controlproceduresrevenues and expenditures and internal control procedures and whether the cash receipts and disbursements made manado city transportation agencies are effective. the analysis method used is the method of analysis of historical data in a way to understand the procedure and the production of cash receipt obtained from the Office of Manado City relationship. use secondary data sources Relations Office of Manado City. Results from this study indicate Relations Office of Manado City has run acceptance procedure and production cash good fit with PP # 24 in 2005 and No. Permendagri. 13th 2006 that is about Government Accounting Standards, and use of the documents and functions are duly authorized.